Secagem e processamento das cascas de maracujá: uma revisão - Silva, Mariana Andrade Alves da (Universidade Federal de São Carlos, 2024)
Nowadays, waste recovery is a much discussed topic in food industries, beeing the passion fruit known as a big waste generator raw material, futhermore, there are lots of diferentes options of destiantion for the generated waste on the passion fruit process. The passion fruit peel drying turned into flour is a well comented way of it’s destination, that way, the presente final course project presentes a literature review focused on the utilization of passion fruit peel on flour production, evaluating diferente drying methods and equipments, as well as their advantages and disadvantages. Others mentioned points are the drying kinetics theory, process mathematical modeling and the comparison of the results of diferentes studys for such production that encompass the passion fruit drying process using: tray dryers with recirculated air; freeze dryer; ultrasound assisted convective dryer and solar dryer. The usually discarted peel, exhibit a big source of nutrientes that justifies its destinations to flour production. The study identified that every method mentioned could have its application justified and presented advantages and disadvantages in differents aspects, turning the global project understanding a recomendable thing. Between the observed methods, the most recommended was tray dryers with air recirculation, as the flour produced was high quality and the costs, in addition to time, were appropriate for different types of processes, encompassing smaller budgets and maintaining the expected quality.
Drying and processing of passion fruit peels: a review
Keywords: Maracujá; Casca; Secagem; Tratamento; Resíduos; Processamento; Farinha; Bandejas; Secadores; Convecção; Condução; Tambor; Liofilização; Radiação; Evaporação; Desidratação; Pulverizadores; Passiflora; Passion fruit; Peel; Drying; Treatment; Residues; Processing; Flour; Tray; Convection; Conduction; Drum; Freeze drying; Radiation; Evaporation; Dehydration; Sprayers; Passiflora; CIENCIAS AGRARIAS::CIENCIA E TECNOLOGIA DE ALIMENTOS::ENGENHARIA DE ALIMENTOS